2007
DOI: 10.1038/sj.npp.1301527
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Unpredictable Stress and Antidepressants Differentially Regulate Expression of the Bcl-2 Family of Apoptotic Genes in Rat Cortical, Hippocampal, and Limbic Brain Structures

Abstract: Apoptosis has been proposed as a contributing cellular mechanism to the structural alterations that have been observed in stress-related mood disorders. Antidepressants, on the other hand, are hypothesized to exert trophic and/or neuroprotective actions. The present study examined the regulation of the major antiapoptotic (Bcl-2, Bcl-xl) and proapoptotic (Bax) genes by repeated unpredictable stress (an animal model of depression) and antidepressant treatments (ADT). In adult rats, exposure to unpredictable str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 77 publications
7
81
2
3
Order By: Relevance
“…An intriguing one is the silencing of genes involved in structural and functional re-organization of learning and memory processes in the context of cell adhesion molecules, since maternal separation can cause irreversible changes in cognitive functions in the offspring. The finding that stress early in life causes delayed impairments of synaptic and cognitive measures of hippocampal function 35,36 requires investigation of permanent and irreversible changes in gene expression, often caused by silencing of genes via methylation of their promoter regions. In the present study we did not detect any increased DNA methylation in the hippocampus of adult mice of the promoters of all genes investigated.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing one is the silencing of genes involved in structural and functional re-organization of learning and memory processes in the context of cell adhesion molecules, since maternal separation can cause irreversible changes in cognitive functions in the offspring. The finding that stress early in life causes delayed impairments of synaptic and cognitive measures of hippocampal function 35,36 requires investigation of permanent and irreversible changes in gene expression, often caused by silencing of genes via methylation of their promoter regions. In the present study we did not detect any increased DNA methylation in the hippocampus of adult mice of the promoters of all genes investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance studies revealed that depression is accompanied by structural changes in the hippocampus, the prefrontal cortex, the amygdala, the anterior cingulate and the basal ganglia [26]. Enhanced apoptosis was detected in the brain structures of rats tested in animal models of depression, such as repeated unpredictable stress [10] and maternal separation [27]. We also demonstrated that [Bcl-2]/[Bax] ratio in the amygdaloid complex of fluoxetine treated traumatized rats was not different from the non-traumatized controls.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine, one of the selective serotonin reuptake inhibitors, shows a strong antidepressive effect and is widely used to augment the actions of serotonin in the nervous system [28][29][30]. The Bcl-2 and Bcl-xl proteins have a well-known antiapoptotic activity and it was formerly demonstrated that the antidepressants upregulated Bcl-2 mRNA in rat limbic structures and frontal cortex [10]. In that study it was demonstrated that fluoxetine did not affect Bcl-2 levels but decreased Bax expression in hippocampal subregions [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations